Inflammation regulates fibroblast growth factor 23 production. Issue 4 (July 2016) - Francis, Connor; David, Valentin
Abstract : Purpose of review: Fibroblast growth factor 23 (FGF23) is a hormone secreted by osteocytes and osteoblasts that regulates phosphorus and vitamin D homeostasis. FGF23 levels increase progressively in chronic kidney disease (CKD), and FGF23 excess might be a causal factor of left ventricular hypertrophy, CKD progression and death. Therefore, understanding the molecular mechanisms that control FGF23 production is critical to design therapies to lower FGF23 levels. The present review focuses on the role of inflammatory stimuli on FGF23 regulation and summarizes recent studies that support a novel framework linking inflammation to FGF23 regulation. Recent findings: Inflammation and iron deficiency, which are common occurrences in CKD, have emerged as novel FGF23 regulators. Recent findings show that inflammation increases FGF23 production in bone through direct and iron-related indirect mechanisms. In these settings, hypoxia-inducible factor (HIF)-1α orchestrates FGF23 transcription in response to inflammation and is primarily responsible for coordinating FGF23 production and cleavage. Summary: We demonstrate that inflammation increases FGF23 production and may contribute to elevated FGF23 levels in CKD. Osseous HIF-1α may represent a therapeutic target to lower FGF23 levels in CKD patients and minimize the negative consequences associated with FGF23 excess.